2018
DOI: 10.1007/s10964-018-0811-z
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Six Decades of Research on Adolescent Behavior and Development

Abstract: These reflections, spanning six decades of involvement with developmental behavioral science, report on several salutary trends that have shaped that field of social inquiry, e.g., its increasingly trans-disciplinary character. They also take note of some of its enduring limitations, e.g., its failure to engage with theory. In addition, the reflections confront some current issues, such as the widespread stereotyping of adolescents as risk takers, and the growing recourse to reductionist explanation. On balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Since the 1970s, there has been consensus that problem behaviors in adolescence cluster together and co‐vary (Jessor, ). As such, it will be important to take into account other, nonsexual risk behaviors as possible contributors to sexual risk taking in models that purport a comprehensive understanding of the unique variation associated with each.…”
Section: Child Maltreatment and Sexual Risk Behaviorsmentioning
confidence: 99%
“…Since the 1970s, there has been consensus that problem behaviors in adolescence cluster together and co‐vary (Jessor, ). As such, it will be important to take into account other, nonsexual risk behaviors as possible contributors to sexual risk taking in models that purport a comprehensive understanding of the unique variation associated with each.…”
Section: Child Maltreatment and Sexual Risk Behaviorsmentioning
confidence: 99%
“…Additionally, the present study indicated the stronger effects of peer support and low expectation for success on adolescent delinquency than other support variables. Moreover, individual factors such as those associated with vulnerability (e.g., felt stress and low expectation for success) were the main factors leading to a friendship with deviant peers who have problem behaviors (73). Such friendships intensify negative intrapersonal emotions and increase the frequency of delinquent behaviors (74).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from the present study could also be explained through other theoretical frameworks. One of these theoretical approaches, which is based on the study of risk-taking behaviors, is the Problem Behavior Theory (PBT) ( Jessor, 2014 ). The PBT analyses the fundamental social-psychological processes involved in risk-taking behaviors, which act as protective and risk factors.…”
Section: Discussionmentioning
confidence: 99%